Welcome :: Homework Help and Answers :: Mathskey.com

Recent Visits

    
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,434 questions

17,804 answers

1,438 comments

48,082 users

Express in A+Bi form?

+2 votes
1.x2-4x=-13
2.2x^2=-3(2x+3)
3.3x^2+3=5x
Help?!?
asked Feb 13, 2013 in ALGEBRA 1 by skylar Apprentice

3 Answers

+1 vote

1). x2 - 4x = -13

Add 13 to each side.

x2 - 4x +13 = 0

Now solve the equation using the factor method.

Compare equation with standard from ax2 + bx + c = 0 and write the coefficients.

a = 1, b = -4 and c = 13.

Quadratic formula: x=[-b±√(b2- 4ac)]/2a

Substitute a = 1, b = -4 and c = 13. in the Quadratic formula.

x = [-(-4)±√((-4)2- 4(1)(13))]/2(1)

x = [4 ±√(16 - 52)]/2

x = [4 ±√(-36)]/2

x = [4 ±√(i236)]/2

x =[ 4 ±√(i236)]/2

x = [4 ±i6]/2

Take out common term 2.

x = 2[2 ±i3]/2

x = [2 ±i3]

Therefore x = 2 + 3i or x = 2 - 3i.

A + Bi form is x = 2 + 3i or x = 2 - 3i.

 
answered Feb 13, 2013 by richardson Scholar
+1 vote

2). 2x2 = -3(2x + 3)

Distribute terms using distributive property:  a(b + c) = ab + ac

2x2 = -6x - 9

Add 6x and 9 to each side

2x2+ 6x + 9 = 0

Now solve the equation using the factor method.

Compare equation with standard from ax2 + bx + c = 0 and write the coefficients.

a = 2, b = 6 and c = 9.

Quadratic formula: x=[-b±√(b2- 4ac)]/2a

Substitute a = 2, b = 6 and c = 9 in the Quadratic formula.

x = [-(6)±√((6)2- 4(2)(9))]/2(2)

x = [-6 ±√(36 - 72)]/4

x = [-6 ±√(-36)]/4

x = [-6 ±√(i236)]/4

x =[ -6 ±√(i236)]/4

x = [-6 ±i6]/4

Take out common term 6.

x = 6[-1 ± i]/4

x = 3[-1 ±i]/2

Therefore x = 3[-1 + i]/2 or x = 3[-1 - i]/2

A + Bi form is x = -3/2 + 3i/2 or x = -3/2 - 3i/2

answered Feb 13, 2013 by richardson Scholar
+1 vote

3). 3x2 + 3 = 5x

Subtract 5x from each side.

3x2- 5x + 3 = 0

Now solve the equation using the factor method.

Compare equation with standard from ax2 + bx + c = 0 and write the coefficients.

a = 3, b = -5 and c = 3.

Quadratic formula: x=[-b±√(b2- 4ac)]/2a

Substitute a = 3, b = -5 and c = 3 in the Quadratic formula.

x = [-(-5)±√((-5)2- 4(3)(3))]/2(3)

x = [5 ±√(25 - 36)]/6

x = [5 ±√(-11)]/6

x = [5 ±√(i211)]/6

x = [5 ±i11]/6

Therefore x = [5 + i11]/6 or x = [5 - i11]/6

A + Bi form is x = 5/6 + i11/6 or x = 5/6 - i11]/6.

answered Feb 13, 2013 by richardson Scholar

Related questions

asked Jan 26, 2015 in PRECALCULUS by anonymous
asked Jul 11, 2014 in PRECALCULUS by anonymous
asked Sep 20, 2014 in PRECALCULUS by anonymous
asked Jan 29, 2015 in PRECALCULUS by anonymous
asked May 10, 2014 in TRIGONOMETRY by anonymous
...